2004
DOI: 10.1103/physrevlett.93.217002
|View full text |Cite
|
Sign up to set email alerts
|

Nernst Effect in Poor Conductors and in the Cuprate Superconductors

Abstract: We calculate the Nernst signal in disordered conductors with the chemical potential near the mobility edge. The Nernst effect originates from the interference of itinerant and localized-carrier contributions to the thermomagnetic transport. It reveals a strong temperature and magnetic field dependence, which describes quantitatively the anomalous Nernst signal in high-Tc cuprates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 40 publications
(56 reference statements)
6
50
0
1
Order By: Relevance
“…In particular, the bipolaron theory accounts for the anomalously large Nernst signal, the thermopower and the insulating-like in-plane low temperature resistance [47,48] as observed [51,64,65,66].…”
Section: Some Normal State Properties Of Cuprates In Fcm a Normmentioning
confidence: 95%
See 2 more Smart Citations
“…In particular, the bipolaron theory accounts for the anomalously large Nernst signal, the thermopower and the insulating-like in-plane low temperature resistance [47,48] as observed [51,64,65,66].…”
Section: Some Normal State Properties Of Cuprates In Fcm a Normmentioning
confidence: 95%
“…Our CTQMC simulations show that with realistic values for the coupling constant, λ ≃ 1, and phonon frequencies, ω ≃ T (a) one can avoid overlap of pairs and get the bose-condensation temperature T c about the room temperature. We believe that the following recipe is worth investigating to look for room-temperature superconductivity [33]: There are strong arguments in favor of 3D bipolaronic BEC in cuprates [3] drawn using parameter-free fitting of experimental T c with BEC T c [41], unusual upper critical fields [42] and the specific heat [43], and, more recently normal state diamagnetism [44], the HallLorenz numbers [45,46], the normal state Nernst effect [47,48], and the giant proximity effect (GPE) [49] as discussed below.…”
Section: And the Mass Renormalization Exponents As Gmentioning
confidence: 99%
See 1 more Smart Citation
“…(Further, a recent calculation [83] has shown that the qp Nernst signal in the dDW state is actually too small to account for the observed e N .) Finally, in a proposed "bipolaron" model, even the Nernst signal observed below T c has been identified as coming from ("localized") quasiparticles [38]. The extreme view is proposed that H m represents the depairing field [65], so that the condensate is destroyed as soon as ρ becomes non-zero.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, acceptance of a vortex origin for e N above T c is by no means unanimous; several models interpreting the Nernst results strictly in terms of quasiparticles have appeared [34,35,36,37,38]. The difficulties may arise because the Nernst experiment is a relatively unfamiliar probe of superconductivity, with a checkered theoretical history [39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%